2016
DOI: 10.1016/j.physa.2015.10.097
|View full text |Cite
|
Sign up to set email alerts
|

Entropic measures of joint uncertainty: Effects of lack of majorization

Abstract: We compute Rényi entropies for the statistics of a noisy simultaneous observation of two complementary observables in two-dimensional quantum systems. The relative amount of uncertainty between two states depends on the uncertainty measure used. These results are not reproduced by a more standard duality relation. We show that these behaviors are consistent with the lack of majorization relation between the corresponding statistics.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…Previous works have found that different entropies lead to contradictory conclusions, where the minimum uncertainty states with one measure are the maximum uncertainty states of the other [22]. Majorization clearly explains this result showing that these contradictions arise because we are dealing with incomparable states [23].…”
Section: Discussionmentioning
confidence: 52%
“…Previous works have found that different entropies lead to contradictory conclusions, where the minimum uncertainty states with one measure are the maximum uncertainty states of the other [22]. Majorization clearly explains this result showing that these contradictions arise because we are dealing with incomparable states [23].…”
Section: Discussionmentioning
confidence: 52%
“…[11] is a quite interesting formulation particularly suited to phase-angle variables. We also show that this encounters fundamental ambiguities when contrasting different slightly different alternative implementations, as it also holds for other approaches [12][13][14].…”
Section: Introductionmentioning
confidence: 56%
“…We have successfully derived meaningful phase-number uncertainty relations from the Weyl form of commutation relations. This can be applied to study phasenumber statistical properties of meaningful field states, especially intermediate states that have already demonstrated interesting properties regarding uncertainty relations [7,13,14].…”
Section: Example: Phase-number Intermediate Statesmentioning
confidence: 99%
“…Lack of majorization relation between two beams just tell us that one must resort to particular criteria, selected according to the particular application, to evaluate whether a beam can be considered of better quality than a second beam or vice versa. The effects of lack of majorization have been studied in other contexts in [23]. A related question is whether exists a beam that majorizes any other beam, that is, an optimal quality beam.…”
Section: Intersecting Lorenz Curves and Contradicting Entropic Bementioning
confidence: 99%